Disordered eating and eating disorders in aquatic sports - Melin, A.; Klungland Torstveit, M.; Burke, L.; Marks, S.; Sundgot-Borgen, J. (International Journal of Sport Nutrition and Exercise Metabolism, 2014)
Disordered eating behavior (DE) and eating disorders (EDs) are of great concern because of their associa- tions with physical and mental health risks and, in the case of athletes, impaired performance. The syndrome originally known as the Female Athlete Triad, which focused on the interaction of energy availability, reproductive function, and bone health in female athletes, has recently been expanded to recognize that Relative Energy Deficiency in Sport (RED-S) has a broader range of negative effects on body systems with functional impairments in both male and female athletes. Athletes in leanness-demanding sports have an increased risk for RED-S and for developing EDs/DE. Special risk factors in aquatic sports related to weight and body composition management include the wearing of skimpy and tight-fitting bathing suits, and in the case of diving and synchronized swimming, the involvement of subjective judgments of performance. The reported prevalence of DE and EDs in athletic populations, including athletes from aquatic sports, ranges from 18 to 45% in female athletes and from 0 to 28% in male athletes. To prevent EDs, aquatic athletes should practice healthy eating behavior at all periods of development pathway, and coaches and members of the athletes` health care team should be able to recognize early symptoms indicating risk for energy deficiency, DE, and EDs. Coaches and leaders must accept that DE/EDs can be a problem in aquatic disciplines and that openness regarding this challenge is important.